PIVOT TABLE ANALISIS BIAYA PROGRAM GIZI DENGAN PERSPEKTIF DISTRICT HEALTH ACCOUNT (DHA): Studi di Kabupaten Sumba Timur tahun 2013 - YENDRIS K SYAMRUTH (JURNAL INFO KESEHATAN, 2014)
Background: Health financing is a major component of the framework of the National Health System , at the district / city are often faced with various problems such as: the tendency anggran used for physical shopping , less operational costs , the tendency to give free local health services to the entire population , the realization of the government budget the late and so forth . Various problems can be detected and identified through the implementation of the District Health account ( DHA ) in the district / city level by using pivot table menu on Excell.Method: The study designed by cross sectional descriptive study. The population in this study is the real cost of the program / activity ( realization ) on a number of government and private institutions in the last year in the East Sumba (2013). The sample was selected from 7 institutions including data household expenditures from Central Office of Statistic/BPS.Results: The budget allocation for the health budget 2013 were reached 9 % under the terms of 36 th 2009 on national Health Act , the health budget allocation according to priority programs such as nutrition is not optimal , the operational budget allocation still focused on indirect activities, the intensity of the activities carried out at the level of nutrition and community health centers, the presence of the role of non- governmental sectors (private , household/ community ) in Nutrition sector financing , potential health insurance system in favor of the Social Security.Conclusion:Nutrition program expenditure of DHA known dimensions is still needed major improvements in operations and directly oriented aspects of public health thanindividual health efforts , beneficiaries of nutrition programs are still a lot of activity in the productive age group (non- human investment)